Nilai Kepahlawanan pada Film Gundala (2019) Karya Joko Anwar pada Teori Anis Matta - M. Ade Putra Bintara; Desyarini Puspita Dewi (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2025)
Gundala (2019) can be seen as a work that not only entertains but also reflects and criticizes Indonesian social realities. This film conveys a message about the importance of courage and solidarity in facing social injustice, as well as raising issues that are relevant to society, such as corruption, economic inequality, and the struggles of the lower classes. This film by Joko Anwar represents heroic values such as courage, patience, willingness to sacrifice, and optimism, which not only inspires but also provides relevant moral learning, especially for the younger generation. This research aims to describe the heroic values displayed in Joko Anwar's Gundala (2019). This research uses a qualitative descriptive research method. The results of this research show that the heroic values found in the film Gundala (2019) by Joko Anwar are in accordance with Matta's (2004) theory. This theory reveals that heroic values contain four symbols, namely Courage, Patience, Willingness to Sacrifice, Optimism and implication.